Vitamin D inhibits bone loss in mice with thyrotoxicosis by activating the OPG/RANKL and Wnt/β-catenin signaling pathways - Xu, Dan; Gao, Hong-Jiao; Lu, Chun-Yan; Tian, Hao-Ming; Yu, Xi-Jie (Frontiers in Endocrinology, 2022)
Objective: Vitamin D and thyroid hormones have crucial roles in bone metabolism. This study aims to explore the effects of vitamin D on bone metabolism in mice with thyrotoxicosis and its mechanisms. Methods: 12-week-old mice were randomly divided into 6 groups (6 mice/group), the control (CON) group, vitamin D (VD) group, low-dose LT4 (Low LT4) group, low-dose LT4+VD (Low LT4+VD) group, high-dose LT4 (High LT4) group, high-dose LT4+VD (High LT4+VD) group, LT4 was provided every day and vitamin D3 every other day for 12 weeks. Thyroid function, 25-hydroxy vitamin D, type I collagen carboxy-terminal peptide (CTX), and type I procollagen amino-terminal peptide were determined. In addition, microcomputed tomography, bone histology and histomorphometry, a three-point bending test, and the mRNA expression of osteoprotegerin (OPG), receptor activator of nuclear factor-κB ligand (RANKL) and β-catenin in bone were conducted. Results: The BMD of lumbar vertebrae and femur decreased and the bone microstructure was destroyed significantly in thyrotoxicosis mice. Addition of vitamin D improved the BMD and bone microstructure only in the low LT4+VD group. Mice with thyrotoxicosis had a significantly higher level of CTX (P<0.05), which was decreased by treatment with vitamin D (P<0.05). The eroded surface per bone surface (Er. S/BS) of the cancellous bone and elongated surface/endocortical perimeter (Er. S/E Pm) of the cortical bone significantly increased in the Low LT4 and High LT4 groups (P<0.05). Treatment with vitamin D significantly decreased the Er. S/BS and Er. S/E Pm. But, treatment with vitamin D did not significantly improve the toughness and rigidity of bones. The ratio of OPG to RANKL and mRNA expression of β-catenin in the Low LT4+VD group were higher than that in the Low LT4 group (P<0.05). Conclusion: In mice with thyrotoxicosis, treatment with vitamin D can inhibit bone resorption and improve the BMD and trabecular bone architecture by increasing the ratio of OPG to RANKL and upregulating the expression of Wnt/β-catenin.